PENGKODEAN TEKS MENGGUNAKAN MODIFIKASI ALGORITMA ELECTRONIC CODE BOOK DAN MERKLE-HELLMAN KNAPSACK - Innafajri Insyirah; Kiswara Agung Santoso; Ahmad Kamsyakawuni (UNEJ e-Proceeding, 2022)
Data security needs to be maintained so that the messages sent to someone are not known by an unauthorized users. One of the data security techniques that can be applied is cryptography. Cryptography is a science and art to keep messages secure when messages are sent from one place to another. In this study, modification of Electronic Code Book and Merkle-Hellman Knapsack algorithms will be applied to secure messages. This research uses Matlab to create a program. The weaknesses of ECB and Merkle-Hellman Knapsack algorithms will be overcome by modifying key and XOR operations. The result of ciphertext is a random numbers which are difficult to understand by unauthorized users. In addition, the message pattern on the same plaintext no longer produces the same ciphertext. Ciphertext can be decrypted well even though the size is two times or longer than plaintext. This is proved by plaintext from the results of decryption is same as the original plaintext. Keywords: Cryptography, Electronic Code Book, Merkle-Hellman Knapsack.